Efektivitas Sistem Produksi dan Manajemen Dokumen Administratif dalam Mendukung Audit Kepatuhan Syariah pada Bank Syariah - Andi Nurwana; Andi Jamaluddin; Reza R; Sri Wahyuni (Precise Journal of Economic, 2024)
Sharia audits are a crucial instrument in ensuring that Islamic banking activities are conducted in accordance with Islamic principles. To support this process, a document and archive management system is required that can provide timely, accurate, and well-organized information. Ineffective management risks hindering the audit process and reducing the reliability of its results. This study aims to evaluate the effectiveness of the document and archive production management system implemented in Islamic banks, specifically in supporting the Sharia audit process. The study focuses on how digital storage systems, archiving procedures, and document distribution flows influence the smooth implementation of audits. The research approach used was a qualitative case study design. Data were obtained through observations of document management practices and a review of policy documents and archives used in the audit process. Analysis was conducted descriptively to illustrate the relationship between the documentation system and audit quality. The results indicate that a digitally integrated document management system can accelerate data access and improve the accuracy of information required by auditors. Furthermore, the existence of standard archiving procedures also contributes to the orderliness and traceability of data relevant to Sharia audits. The results show that structured and digitized document and archive management plays a central role in supporting transparent and efficient sharia audits. Therefore, continued development of technological infrastructure and human resource training is necessary to ensure optimal system performance